2014
DOI: 10.1371/journal.pone.0098961
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive Agents and Risk of Parkinson's Disease: A Nationwide Cohort Study

Abstract: Background and PurposeHypertension has been associated with Parkinson's disease (PD), but data on antihypertensive drugs and PD are inconclusive. We aim to evaluate antihypertensive drugs for an association with PD in hypertensive patients.MethodsHypertensive patients who were free of PD, dementia and stroke were recruited from 2005–2006 using Taiwan National Health Insurance Database. We examined the association between the use of calcium channel blockers (CCBs), angiotensin converting enzyme inhibitors (ACEI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(75 citation statements)
references
References 29 publications
1
74
0
Order By: Relevance
“…First, the confounder of usage of antihypertensive drugs could not be adjusted, which is a very important factor affecting the association between hypertension and the risk of PD. Some studies [14,51] found the use of antihypertensive drugs could reduce the risk of PD. Second, confounders adjusted in studies were different, which could affect the association between hypertension and the risk of PD.…”
Section: Discussionmentioning
confidence: 99%
“…First, the confounder of usage of antihypertensive drugs could not be adjusted, which is a very important factor affecting the association between hypertension and the risk of PD. Some studies [14,51] found the use of antihypertensive drugs could reduce the risk of PD. Second, confounders adjusted in studies were different, which could affect the association between hypertension and the risk of PD.…”
Section: Discussionmentioning
confidence: 99%
“…Parkinson's disease, 35,36,62,63 whereas others did not find a significant effect. 64,65,66,67 However, the consensus based upon systematic review of all available literature is that treatment with calcium channel blockers does appear to reduce the risk of Parkinson's disease 68,69 although the mechanism by which they do so is not completely understood.…”
Section: Introductionmentioning
confidence: 85%
“…Patients were classified as hypertensive if they had at least 1 hospital admission with a diagnostic code of hypertension (ICD9-CM code 401) or ≥2 outpatient visits with a hypertension diagnostic code. 32,33 Statistical tests for interaction were conducted.…”
Section: Discussionmentioning
confidence: 99%